If a + b = 6, what is the value of 3a + 3b?
A = 3B = 5 ___________ 2 ( 3A + B) = 2 (9 + 5) = 2 (14) = 28
(3b)5 = 243 b5The actual numerical value depends on the value of ' b ',and it changes instantly any time ' b ' changes.
3b+4 = b+12 3b-b = 12-4 2b = 8 b = 4
the answer is 11. b = 11 b is unknown value. We need to find out what is "b" to make the statement true. write the given statement 3b + 15 = 48 Subtract 15 from both sides 3b + 15 -15 = 48 - 15 3b = 33 Divide both sides by 3 3b/3 = 33/3 b = 11
let A = first card and let B = second card; then A = 3B and B = A-6; since A = 3B then B = (3B) - 6; solve B = 3 and A = 9
If a + b = 6, what is the value of 3a + 3b?
A = 3B = 5 ___________ 2 ( 3A + B) = 2 (9 + 5) = 2 (14) = 28
(3b)5 = 243 b5The actual numerical value depends on the value of ' b ',and it changes instantly any time ' b ' changes.
It is an equation and the value of b is 3
If b = 5 then 15-10 = 5
3b+4 = b+12 3b-b = 12-4 2b = 8 b = 4
i d know
the answer is 11. b = 11 b is unknown value. We need to find out what is "b" to make the statement true. write the given statement 3b + 15 = 48 Subtract 15 from both sides 3b + 15 -15 = 48 - 15 3b = 33 Divide both sides by 3 3b/3 = 33/3 b = 11
your expression is this... 2a+3b with the information given you can not solve this problem . There is no information given whatsoever that in any way constrains the value of 'a' or 'b'. They can be anything you want them to be.
-2
The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3